Development Of Online Attendance Application With Time And Location Validation At Satpol Pp South Tangerang: Pengembangan Aplikasi Absensi Online Dengan Validasi Waktu Dan Lokasi Di Satpol PP Tangerang Selatan - Syamsu Hidayat; Muhamad Rifki Ramadhan; Joko Susilo (NUANSA INFORMATIKA, 2025)
In order to solve the inefficiencies and errors in manual attendance at the Satpol PP office in South Tangerang, this study creates a web-based attendance system.  The Laravel framework is used to construct the system, and GPS and reverse geocoding are incorporated to verify the locations of check-in and check-out.  The system design is supported by UML diagrams, and structured attendance data is handled using a MySQL database.  The Black Box Testing technique verifies that the system's essential features operate as planned.  The outcomes demonstrate enhanced precision, real-time tracking, and simplified reporting.  To improve system usability and dependability, future suggestions call for including mobile apps, facial recognition, and predictive attendance analytics. In order to increase productivity, precision, and openness at the Satpol PP office in South Tangerang.